The Effect of Social Capital and Social Support toward Elderly Welfare Members of Home Care Program - Mariani, Mariani; Kadir, Subhan; Hariadi, Sunarru Samsi (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The purpose of the research is to analyze the influence of social capital and social support toward elderly welfare, involving 35 elderly participants in Home Care Program as respondents. This research is quantitative method. The results showed that although social capital and social support are at a high level, but they did not necessarily have impact on improving the welfare for the elderly. The result of regression analysis showed no significant effect of social capital (t = 0.812. P> Î± 0.05) and social support (t = 0.333. P> Î± 0.05) separately and collectively (F = 0.552. P> Î± 0,05) on the welfare of the elderly. The value of R = 0.191 indicates a very weak relationship between social capital and social support to the elderly welfare. Contribution influenced of social capital and social support to the elderly welfare is only 3.6persen (R2 = 0.036). The rest of 96.4 persen are caused by other factors not included in the variables of this study. The effect of social capital and social support to welfare of the elderly is on physical and psychosocial aspects only. Other aspects included welfare indicators consist of environmental conditions, especially housing, access to public and social services, and household economic are not maximal. It is recommended that home care program further to strengthen social capital and social support should be specifically directed to elderly welfare. The program should be implemented by encouraging active participation of community in order to continue the program without depending external parties.